ESSENCE OF FRAILEJÓN: SUSTAINABLE PRODUCT PROPOSAL IN COLOMBIA - PÁEZ ARIAS, DANIEL FERNANDO
Frailejones (subtribe Espeletiinae, Asteraceae) are the most representative plants of the Colombian moorlands, known mainly for their ability to collect water from their environment and play a fundamental role in the conservation or maintenance of the moorlands. For this reason entities such as National Natural Parks of Colombia constantly develop programs for the propagation of some 144 known species, composed in 8 genera of the subtribe in the different moorlands of the territory; showing the case of the Sanctuary of Fauna and Flora Guanentá - Alto Río Fonce, together with the support of the Peñas Negras Military Base apply basic schemes of processes in which it is characterized, harvesting, planting and if necessary transporting this type of plant species for ecological restoration and impact mitigation projects with these specimens. Currently, the importance of the species has only been contemplated from its ecosystem function but no initiative has been applied for extraction of its essence and its cosmetic or medicinal use; therefore it is proposed to make use of the cap of frailejón coming from the flower, being a residue derived from one of the processes of propagation of plant species, which is not given a use or treatment that generates some kind of benefit or support to the Special Administrative Unit in charge of protected areas in Colombia.